Influence of Repeated Cycles of Rhythmic Cryostimuli (â€“120Â°Ð¡) on Ultrastructure Organization of Myocardium Blood Capillaries Endotheliocytes in Dynamics of Rats’ Aging - Martynova, Yuliya V.; Babiichuk, Vladislav G. (Problems of Cryobiology and Cryomedicine, 2015)
N/A